Sistem Informasi Perhotelan Berbasis Web Service, Studi Kasus Di Pulau Lombok - Riris Parahita; Ida Bagus Ketut Widiartha; Ariyan Zubaidi (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2017)
Abstract - Hotel located on the Lombok island has a considerable amount. Integrating multiple hotel information systems into a single container that can be accessed by visitors. The purpose of this research is to build a website hotels at the island Lombok using web services technology to facilitate users in finding information and booking hotel rooms. Implementation of the web service technology, the method used to construct the hotels Lombok hotels webiste are SOAP and implements a distributed database system that connects the DBMS of the same type, compatible, structure and description of the same data. To know the system is successfully implemented, then the testing of the system by using the black box. Other than that, testing the questionnaire to 30 students as respondents. Based on the data obtained in this research will be calculated MOS value (Mean Opinion Score), so as to get the average value of MOS is 91.32%. The results of these tests show that the system is web-based information hotel Lombok service that has been implemented is a good system and easily understood by users. Keywords: Hotels, web services, SOAP.